Characteristics of attentional bias in adolescents with major depressive disorders: differentiating the impact of anxious distress specifier - Yang, Rong; Zheng, Hongyu; Cao, Xiaomei; Mo, Daming; Li, Mengting; Liu, Wenyuan; Zhong, Hui (Frontiers in Psychiatry, 2024)
Background: No consistent conclusion has been reached regarding the attentional bias characteristics of adolescents with major depressive disorders (MDD), and unexamined co-occurring anxiety distress may contribute to this inconsistency. Methods: We enrolled 50 MDD adolescents with anxiety distress, 47 MDD adolescents without anxiety distress, and 48 healthy adolescents. We measured attentional bias using a point-probe paradigm during a negative-neutral emotional face task. Reaction time, correct response rate, and attentional bias value were measured. Results: MDD adolescents did not show a negative attentional bias; MDD adolescents with anxiety distress exhibited longer reaction time for negative and neutral stimuli, lower correct response rate for negative stimuli. Hamilton Anxiety Scale scores were positively correlated with reaction time, negatively correlated with correct response rate, and not significantly correlated with attentional bias value. Limitations: The cross-sectional design hinders causal attribution, and positive emotional faces were not included in our paradigm. Conclusions: Negative attentional bias is not a stable cognitive trait in adolescents with MDD, and avoidance or difficulty in disengaging attention from negative emotional stimuli may be the attentional bias characteristic of MDD adolescents with anxiety distress.